Genealogical and morphological analysis of Lusitano purebred horses participating at international dressage competitions - Bartolomé, E.; Milho, S.; Prazeres, J. (Research in Veterinary Science, 2019)
The International Equestrian Federation (FEI) ranks horses participating in dressage tests resulting in a prestigious list where equestrians would like to see their horses ranked.